The role of race/ethnicity in cerclage efficacy. (2nd October 2017) - Fryer, Kimberly; Keiser, Sharon; Trofatter, Kenneth; Eichelberger, Kacey Y.; Heberlein, Emily
Abstract: Objective : To measure the impact of race/ethnicity on cerclage efficacy, as measured by the prevalence of spontaneous preterm birth (PTB), in a cohort of patients with history-indicated, ultrasound-indicated and physical-exam indicated cerclages. Methods : We conducted a retrospective cohort study of patients undergoing history-indicated, ultrasound-indicated and physical-exam indicated cerclage placement from January 2003 to July 2013 at a tertiary care hospital. Patients' race/ethnicity was self-declared. Our primary outcome was spontaneous preterm birth (SPTB) < 37 weeks. Subgroup analyses were performed for each of the three indications for cerclage. Results : One hundred and eighty-one subjects met inclusion criteria. Forty-seven percent self-identified as non-Hispanic black (NHB), 12% as Hispanic and 41% as non-Hispanic white (NHW). There was no significant difference in the prevalence of SPTB < 37 weeks between the three race/ethnicity groups (33% versus 19% versus 40%, respectively, p  = 0.22), nor for SPTB less than 34 or 28 weeks. Finally, there was no difference in SPTB prevalence by race after controlling for smoking, history of CKC/LEEP, and 17-OHPC with logistic regression. Conclusion : Race/ethnicity does not appear to be associated with cerclage efficacy, as measured by the risk of SPTB, in a cohort of patients with history-indicated, ultrasound-indicated and physical-exam indicated cerclages.